1955
DOI: 10.1139/v55-106
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of the Hydration of Calcium Oxide

Abstract: Three sarnples of c a l c i~~~n oxide, designated as .A, B, ancl C, \\.ere preparecl from c a l c i~~m carbonate labelled with calci~~m-45. : \ \vas heated to constant weight a t 700°C.; B was hcated an additiollal three hours a t 1400 to l55OoC.; and C was heated six hours a t the same temperature. 'The samples \\.ere hydratetl in a supersaturated lime solution a t 21°C., the develop~llent of activity and the changes in collcentratiol~ of thc solution being deterlnined. l'he activity cnterillg the solution ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1960
1960
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 2 publications
(5 reference statements)
0
17
0
Order By: Relevance
“…[11,45,73], and (b) so-called ''through-solution'' or ''wet hydration''. For this second mechanism, it is at present unclear whether (a) the CaO first dissolves in the solution phase (water) and subsequently precipitates as Ca(OH) 2 [12,84,101,128], or (b) direct conversion of CaO into Ca(OH) 2 occurs, as in vapour phase hydration, followed by (partial) dissolution (and re-precipitation) of the Ca(OH) 2 formed [12,113].…”
Section: Model For Foc Development and Application To Cao Hydrationmentioning
confidence: 99%
“…[11,45,73], and (b) so-called ''through-solution'' or ''wet hydration''. For this second mechanism, it is at present unclear whether (a) the CaO first dissolves in the solution phase (water) and subsequently precipitates as Ca(OH) 2 [12,84,101,128], or (b) direct conversion of CaO into Ca(OH) 2 occurs, as in vapour phase hydration, followed by (partial) dissolution (and re-precipitation) of the Ca(OH) 2 formed [12,113].…”
Section: Model For Foc Development and Application To Cao Hydrationmentioning
confidence: 99%
“…As pointed out in reference 7, these effects tend to nlalte the activity the same for all mechanisms in the later stages of reaction. Thus for the C3AHs-C3AZ3H31 reaction, assuming nl --t 0, the activity \vould alnrays be close to (from equation [13] …”
Section: Stabilitiesmentioning
confidence: 78%
“…could also be obtained as a product of a solid-liquid reaction. Samples of C,AH, and C3AZH12 weighing about 0.05 g were added to 50-cc portions of a inixed Ca(OH)?-CaSOd solution such that each portion contained 13.334 X lo--' mole calcium and 6.45 X 10-Qlnole sulphate, and were shaliel~ inside a n oven for periods of up to 7 days. For temperatures of 70" and 90" C the reaction products were consistelltly acicular, and solution analyses confirmed that C3AZ3H31 had formed.…”
Section: Reactions At Elevated Temperaturesmentioning
confidence: 99%
“…solid-liquid reactio~is were described a s following mechanisms based on the clegree of mixing (1,3,1). There is reason to believe, however, that the procluct solids in a t least t\\~o of the reactions (the hydrations of CaSOl.+H20 (3) ant1 CaO (4)) exhibit rapicl, ~uultidirectional external excl~ange.~ T h e reactions in question are therefore perhaps better represe~lted in terms of "surface" or "internal" mechanislns; passage through solution may still have occurrecl, but was not rigorously demonstrated.…”
Section: Previously S T~~d I E Dmentioning
confidence: 99%
“…+I-120 (3), and CaO (4); the conversion of illsoluble sulphates to carbonates (5, p. 585); and the reactions described in reference 6. Innumerable variations in the details of solid-liquid reaction mechanisms are undoubtedly possible; however, the mechanisms will tend to fall into general classes or systems which represent to first approximation the liinits of experiinental distinguishability. One such system, much usecl in past work (1,3,4), considers the degree of mixing with the liquid of successively reacting portions of the reacting solid (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%